Effects of ?-lipoic acid and resveratrol on rats cancer model induced by 7, 12-DMBA - Bahşi, Muammer; Ökkeş; Yılmaz, Okkes; Yilmaz (My University, 2015)
?-Lipoic acid (LA) has been intensely investigated as a therapeutic agent for several diseases, including hepatic disorder and diabetic polyneuropathy. However, the effects of LA or its reduced form, dihydrolipoic acid (DHLA), on cancer chemoprevention has been slightly reported. In the present study, we examined the effects of DHLA/LA on rat cancer model induced by 7,12-dimethylbenz(a)anthracene (DMBA). Another therapeutic agent; Resveratrol, was found in high concentrations in berry, grape, peanut, pine and wine and act as an antioxidant and antimutagen. In addition, resveratrol and ?-lipoic acid inhibited the development of preneoplastic lesions in carcinogen-treated rat cancer model. Datas in this study suggest that resveratrol and ?-Lipoic acid, a common constituent of the human diet, merits investigation as a potential cancer chemopreventive agent in humans.
Keywords: Biyoloji; Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Onkoloji; Biyokimya ve Moleküler Biyoloji